Home-Birth Experiences on Wartime and Post-War Kakeroma Island and Traditional Midwives Called “Toriage Basan” - YOSHIOKA, Kaori; YOSHITOME, Atsuko (JOURNAL OF THE JAPANESE ASSOCIATION OF RURAL MEDICINE, 2010)
[Objective] To document pregnancy and home-birth experiences of a woman on Kakeroma Island from 1945 to 1954 for reviewing the present environment of childbirth. [Methods] We conducted interviews with an old woman and asked about her life, pregnancy, delivery, and child-rearing experiences as a Toriage Basan on Kakeroma Island during and after the war. [Results] The woman (named Mieko Nakamura) was 88 years old at the time of the interview. She was married at the age of 21 and gave birth to seven children. During the pregnancy, she planted rice, worked in the field, and gathered firewood until just before delivery. She asked her mother-in-law what to do in preparation for delivery and brought her knowledge of childbirth and child care up to date by reading books. In those days, women in childbirth were attended upon by Toriage Basan, who had given birth to children, since there were no obstetricians or registered midwives. Because parous women traditionally attended births as Toriage Basan, Mrs. Nakamura she followed the custom and delivered eight babies. [Discussion] In close-knit communities, the knowledge of childbirth and the skills to deliver children have been passed down from generation to generation. It is considered that mothers took it upon themselves as a sense of mission or responsibility to transmit the skills on to the next generation. Pregnancy to child-rearing experiences seem to have contributed to the development of abilities in women to tide over difficulties on their own.